TINJAUAN YURIDIS PERUBAHAN NAMA SESEORANG PADA AKTA KELAHIRAN BERDASARKAN PERATURAN PRESIDEN NO/ 96 TAHUN 2018 TENTANG PERSYARATAN DAN TATA CARA PENDAFTARAN PENDUDUK DAN PENCATATAN SIPIL DI PENGADILAN NEGERI ATAMBUA - Benu, Veni Mariadi; Mauritsius, Darius; Pello, Helsina Fransiska (Petitum Law Journal, 2025)
This article analyzes the change of a person's name on a birth certificate based on presidential regulation no. 96 of 2018 in the Atambua district court. A person's name is an important factor in his identity as a subject, while a birth certificate is the first population document obtained by the community since his birth which contains his name and other identities. The change of a person's name on a birth certificate becomes an important matter that should be seen in terms of implementation procedures, obstacles to implementation and legal consequences, which are formulated into problems in the research as follows: (1) What are the implementation procedures for changing one's name on a birth certificate at the Atambua District Court based on Presidential Regulation Number 96 of 2018 concerning Requirements and Procedures for Population Registration and Civil Registration (2) What are the inhibiting factors in changing one's name on a birth certificate quote (3) What are the legal consequences of changing one's name on a birth certificate at the Atambua District Court. This research is empirical juridical in nature which requires primary data sources or field research which requires interview methods and document studies. The results of the study said that the implementation of a person's name change on a birth certificate at the Atambua District Court was slightly different from Presidential Regulation No. 96 of 2018 but still followed the existing requirements, the most obstacles in its implementation were low education, procedures that were considered difficult and the non-acceptance of applications at the Court. The legal consequences are legal certainty and multiple identities.